2013
DOI: 10.1308/003588413x13511609954734
|View full text |Cite
|
Sign up to set email alerts
|

Should prophylactic antibiotics be used routinely in epistaxis patients with nasal packs?

Abstract: IntroductionThe current mainstream practice in otolaryngology departments relating to the use of prophylactic antibiotics in epistaxis patients requiring nasal packing is highly variable. This is due primarily to the lack of any validated guidelines. As such, we introduced a new treatment algorithm resulting in significant reduction of use in the systemic antibiotics, with emphasis instead on the use of topical antibiotics. The results were validated through a complete audit cycle.MethodsA total of 57 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 5 publications
0
18
0
2
Order By: Relevance
“…Nasal culture results at the time of packing removal have been overall similar to those of nonpacking nasal cavities [40]. A recent study by Biggs et al [39] reviewed the use of antibiotics in patients with anterior nasal packs for epistaxis, showing that there were no difference in outcomes such as infective nasal symptoms, rebleeding, or readmission, even though antibiotic use fell 58% during the time period studied. These authors suggest that use of a topical antibiotic might be a more effective and cheaper alternative to oral antibiotics.…”
Section: Evidence For Antibiotics With Nasal Packingmentioning
confidence: 86%
See 1 more Smart Citation
“…Nasal culture results at the time of packing removal have been overall similar to those of nonpacking nasal cavities [40]. A recent study by Biggs et al [39] reviewed the use of antibiotics in patients with anterior nasal packs for epistaxis, showing that there were no difference in outcomes such as infective nasal symptoms, rebleeding, or readmission, even though antibiotic use fell 58% during the time period studied. These authors suggest that use of a topical antibiotic might be a more effective and cheaper alternative to oral antibiotics.…”
Section: Evidence For Antibiotics With Nasal Packingmentioning
confidence: 86%
“…From 2009 to 2013, studies have failed to demonstrate improvement in outcomes or reduction in adverse events with routine use of oral antibiotics [39][40][41]. Nasal culture results at the time of packing removal have been overall similar to those of nonpacking nasal cavities [40].…”
Section: Evidence For Antibiotics With Nasal Packingmentioning
confidence: 99%
“…In this study, seven subjects with postoperative anterior packing underwent its removal 48 h later, so there was no need for a systemic antibiotic. The principle of preventing infection due to nasal packing is applicable not only to postoperative patients but also those with epistaxis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Porous materials such as cotton are more prone to collect bacteria and are not as easily cleaned. Multiple studies throughout the years have shown that cotton‐based products (e.g., tampons and nasal packs) may lead to life‐threatening infections, including toxic shock syndrome due to the exotoxin from S taphylococcal aureus or simple skin infections. Cotton and other absorbable bolsters are able to soak up excess drainage, thus taking a longer time to dry, leading to skin maceration and breakdown.…”
Section: Discussionmentioning
confidence: 99%